Reconstruction of the Implementation of Direct General Election Law: (A Study of the Implementation of General Election Law Number: 7 of 2017) - Suparnyo; Subarkah (Technium Social Sciences Journal, 2020)
The Indonesian Constitution that has been directed to provide social welfare through a legal system and popular democracy led by wisdom in the representation of representatives has become the legal ideals (Rechsidee) of the Indonesian people as intended in the opening of the 1945 Constitution of the Republic of Indonesia. The phrase “inner wisdom” is interpreted as a unity of words and the core “deed” of which is taqwa, and “deliberations amongst representatives” is interpreted as representative democracy in the MPR, instead of direct democracy which actually produces something that is counterproductive.